2005
DOI: 10.1098/rspb.2004.2963
|View full text |Cite
|
Sign up to set email alerts
|

Low effective population size and evidence for inbreeding in an overexploited flatfish, plaice (Pleuronectes platessaL.)

Abstract: Overexploitation and subsequent collapse of major worldwide fisheries has made it clear that marine stocks are not inexhaustible. Unfortunately, the perception remains that marine fishes are resilient to large population reductions, as even a commercially 'collapsed' stock will still consist of millions of individuals. Coupled with this notion is the idea that fisheries can, therefore, have little effect on the genetic diversity of stocks. We used DNA from archived otoliths collected between 1924 and 1972 toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
132
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 44 publications
18
132
1
Order By: Relevance
“…We found a non-random distribution of individuals in relation to size and sex, and relatively high F IS levels within most sample-sets. This suggests that standard population comparisons may not be appropriate in this species and that some kind of temporal Wahlund effect may be operating (Hoarau et al, 2005), for example, because of sweepstake effects (in which most surviving larvae are from a relatively small number of females) every breeding season (Hedgecock, 1994). In common with previous studies of A. rostrata, we found that samples from off Greenland contained both males and females, whereas samples from elsewhere consisted almost entirely of females.…”
Section: Discussionmentioning
confidence: 99%
“…We found a non-random distribution of individuals in relation to size and sex, and relatively high F IS levels within most sample-sets. This suggests that standard population comparisons may not be appropriate in this species and that some kind of temporal Wahlund effect may be operating (Hoarau et al, 2005), for example, because of sweepstake effects (in which most surviving larvae are from a relatively small number of females) every breeding season (Hedgecock, 1994). In common with previous studies of A. rostrata, we found that samples from off Greenland contained both males and females, whereas samples from elsewhere consisted almost entirely of females.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hoarau et al (2005) reported that their low N e /N ratio for North Sea plaice could be explained by inbreeding. This inference may essentially be correct, with the distinction that population subdivision (that is, inbreeding), may have introduced a downward bias into N e , in addition to inbreeding effects reducing N e through biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no regular collection of data to show changes in the level of genetic diversity of cobia over time. Additionally, it has been shown that a high or unchanged level of genetic diversity may not be able to fully reflect the status of population exploitation if the effective population size of the species is large (Hoarau et al 2005). However, due to the small and undervalued domestic market for cobia, it is possible that cobia fisheries in Thailand may not yet be overexploited.…”
Section: Status Of Cobia Population and Implication For Fisheries Manmentioning
confidence: 99%